2004
DOI: 10.1021/bi048399h
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the DNA Binding Tendencies of the Transition State Regulator AbrB

Abstract: Global transition state regulator proteins represent one of the most diverse classes of prokaryotic transcription factors. One such transition state regulator, AbrB from Bacillus subtilis, is known to bind more than 60 gene targets yet displays specificity within this target set by binding each promoter with a different affinity. Microelectrospray ionization mass spectrometry (microESI-MS), circular dichroism, fluorescence, UV spectroscopy, and molecular modeling were used to elucidate differences among AbrB, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 39 publications
4
55
0
Order By: Relevance
“…Local variations of the DNA helix configurations (e.g., minor groove width and degree of propeller twisting, etc.) contribute to the differential binding proclivities of AbrB (3). Here, we demonstrated that the replacement of local AT-rich sequence stretches within the AbrB binding region by GC-rich oligonucleotides decreases affinity toward AbrB.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Local variations of the DNA helix configurations (e.g., minor groove width and degree of propeller twisting, etc.) contribute to the differential binding proclivities of AbrB (3). Here, we demonstrated that the replacement of local AT-rich sequence stretches within the AbrB binding region by GC-rich oligonucleotides decreases affinity toward AbrB.…”
Section: Discussionmentioning
confidence: 75%
“…The functional form of AbrB has been described as a homotetramer rather than as a homodimer (2,20). DNAbinding and dimerization functions are located in the N-terminal domain (AbrBN), and the C-terminal domain is responsible for the tendency towards multimerization (2,3,20,21). In this study, we have not addressed the oligomeric state of AbrB, but gel filtration suggested that AbrB could form oligomers containing more than four subunits (see Fig.…”
Section: Discussionmentioning
confidence: 95%
“…During in silico analyzation of the DNA sequence of the two promoter regions, it was not possible to find putative recognition motifs, since a search for highly similar DNA stretches failed to give possible hits. Interestingly, AbrB from B. subtilis is well known for its significant promiscuity in DNA recognition (6,7,42) and the comparison between the described target regions reveals no apparent base sequence that can be defined as an AbrB consensus binding site (48).…”
Section: Vol 190 2008mentioning
confidence: 99%
“…High-affinity sites of AbrB-DNA interactions selected using in vitro methods do show convergence to a consensus, but sequences resembling this consensus are rarely found in the chromosomal sites (50, 53). It has been hypothesized that AbrB achieves binding specificity by recognizing three-dimensional DNA architectures that are shared by a finite subset of base sequences (5,40,42,45,53). A major factor accounting for what has been termed the "limited promiscuity" of AbrB-DNA interactions is believed to be the dynamic flexibility in the DNA-binding domain of the protein; this flexibility allows it to conform to different targets with thermodynamically favorable contacts (4, 6, 47).…”
mentioning
confidence: 99%